Influence of Eugenol on the Organization and Dynamics of Lipid Membranes A Phase-Dependent Study - Meher, Geetanjali (Langmuir : the ACS journal of surfaces and colloids, 2018)
Eugenol is known for its antimicrobial effects against microorganisms responsible for infectious diseases in humans, food-borne pathogens, and oral pathogens. In spite of several reports on the antimicrobial function of eugenol by modulating the structural properties of cell membranes, there is limited information on the influence of eugenol in the lipid membrane. In this work, we explored the effect of eugenol on the organization and dynamics of large unilamellar vesicles (LUVs) of DMPC using the intrinsic fluorescence of eugenol and an extrinsic hydrophobic probe, DPH, in varying phases. The organization and dynamics of the bilayers of DMPC vesicles were monitored by utilizing varieties of steady-state and time-resolved fluorescence measurements. Our results show that eugenol stabilizes the gel phase and elevates the phase-transition temperature of DMPC in a concentration-dependent fashion. Fluorescence lifetime measurements demonstrate that higher eugenol-induced water penetration was observed in fluid-phase membranes. Time-resolved anisotropy measurements demonstrate that eugenol reduces the semiangle of DPH wobbling-in-a-cone in gel-phase membranes, whereas the semiangle remains unaffected in fluid-phase membrane. This implies that the eugenol further orders the gel-phase membrane, and this could be a plausible reason for the eugenol-dependent elevation of the phase-transition temperature of DMPC. We envisage that these results will contribute important information to understand the interaction of eugenol with biological membranes